Effect of the Density and the Refractive Index on the Toxicity of Imidazolium Ionic Liquids: A study of Ionic Interactions. (December 2018) - Zaini, Dzulkarnain; Khan, Muhammad Ishaq; Shariff, Azmi Mohd; Athar, Muhammad; Shamim, Muhammad Yasir
Abstract: Ionic Liquids (ILs) has got a significant attraction in the academia as well as in industries because of the salient characteristics and flexibility in tune-ability. The ionic nature and a huge number of possible combinations of cations, anions and functional groups make ILs potential candidates for industrially suitable materials. However, the toxic nature of ILs is still a big challenge. To overcome this problem, knowledge of the interactive mechanism of the ionic species of ILs is desired. In current work, we have investigated the ionic interaction of ILs by studying the effect of intensive properties of ILs "density" and "refractive index" of imidazolium NTf2 and PF6 ILs. Result produced in the current provided relationship of toxicity of ILs to their refractive indices and densities. The findings of current work are helpful to understand the mechanism of the toxic behavior of ILs.